Indian cultures as heritage: contemporary pasts - "Thapar, Romila" (New Delhi, 2018)
Every society has its cultures: the patterns of how people live and express themselves and how they value objects and thoughts. What constitutes Indian heritage and cultures has been much discussed. Romila Thapar begins by explaining how the definitions of the concept of culture have changed since the last three centuries and hence require added attention. Cultures when defined by drawing on selected items and thoughts from the past, remain relatively unknown, except to a few. Yet each has a context and meaning relating them to the past and to their significance as a contemporary presence. Contexts, often regarded as unconnected to culture, can to the contrary, be quite illuminating. Thapar touches on a few of these, ranging from objects that identify cultures, to ideas that shape cultures, such as social discrimination, the role of women and attitudes to science and knowledge. Thought-provoking books such as this spark debate and the debate may lay to rest some current shibboleths about India?s culture.
Keywords: India - Civilization